Effective school leadership in challenging times a practice-first, theory-informed approach - Browne, Liz 1952- (Routledge, 2021)
"Education Leadership has been subject to a period of turmoil with rapid social change, political demands for excellence, economic pressures for austerity and the influence of technology impacting on leadership roles in multiple ways. This book draws on real examples of practice to identify the key challenges facing educational leadership and how these might be overcome drawing on recent research and interventions that have impacted positively on learner outcomes and teacher retention. Covering all aspects of leadership including school improvement, vision and values, working with partners and leading change, the book launches the concept of atomic leadership, advocating small steps to change for maximum momentum and large-scale impact. It reveals how leaders can cooperate to trial new ways of learning and disseminate their successes and failures with a new honesty and openness about what works in our schools. With reflective tasks in every chapter, this text will inspire debate and inform discussion at staff meetings and is essential reading for all school leaders as well as those undertaking Masters level courses in Educational Leadership and or pursuing the National Professional Qualifications in Leadership"--